2022
DOI: 10.3847/1538-4357/ac8876
|View full text |Cite
|
Sign up to set email alerts
|

Hundreds of Low-mass Active Galaxies in the Galaxy And Mass Assembly (GAMA) Survey

Abstract: We present an entirely new sample of 388 low-mass galaxies (M ⋆ ≤ 1010 M ⊙) that have spectroscopic signatures indicating the presence of massive black holes (BHs) in the form of active galactic nuclei (AGNs) or tidal disruption events. Of these, 70 have stellar masses in the dwarf galaxy regime with 108 ≲ M ⋆/M ⊙ ≲ 109.5. We identify the active galaxies by analyzing optical spectra of a parent sample of ∼23,000 low-mass … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 100 publications
(206 reference statements)
4
7
0
Order By: Relevance
“…The descendants of the galaxies hosting overmassive black holes at 0.35 < z < 1 in the simulation show a wide distribution of stellar masses, with 13% of them having M *  10 9 M e and hence to host overmassive black holes at z = 0 (as already found observationally in a few cases; e.g., Secrest et al 2017;Salehirad et al 2022). On the other hand, 35% of them (roughly one-third) evolve into ordinary M * > 10 10 M e galaxies, hence becoming "normal" systems (i.e., massive galaxies hosting SMBHs).…”
Section: Discussionsupporting
confidence: 72%
“…The descendants of the galaxies hosting overmassive black holes at 0.35 < z < 1 in the simulation show a wide distribution of stellar masses, with 13% of them having M *  10 9 M e and hence to host overmassive black holes at z = 0 (as already found observationally in a few cases; e.g., Secrest et al 2017;Salehirad et al 2022). On the other hand, 35% of them (roughly one-third) evolve into ordinary M * > 10 10 M e galaxies, hence becoming "normal" systems (i.e., massive galaxies hosting SMBHs).…”
Section: Discussionsupporting
confidence: 72%
“…The FWHM of the broad Hα line from the 1″ diameter circular aperture centered on Nucleus 1 is 446 ± 17 km s −1 . The total luminosity of the broad component is ≈ 1.5 × 10 38 erg s −1 , comparable to that found in the well-known type 1 dwarf AGN NGC 4395 (Brum et al 2019), and considerably lower than the broad-line luminosities of previously identified low-mass broad-line AGNs in the dwarf-galaxy population (e.g., Greene & Ho 2007;Reines et al 2013;Salehirad et al 2022), as might be expected for a galaxy with a stellar mass at least 1-3 orders of magnitude lower than that of any previous dwarf galaxy with an identified broad-line AGN (e.g., Baldassare et al 2016;Salehirad et al 2022). Note that the broad line disappears when the extraction aperture size is increased to match the SDSS aperture size, indicating that its origin is from an extremely compact region centered on the nucleus.…”
Section: Broad-line Detectionsupporting
confidence: 69%
“…Salehirad et al (2022) identified 388 low mass AGN hosts in the GAMA DR4 equatorial and G23 regions consistent with our definition of low mass (log M * /M ≤ 10). Of this sample, 53 lie in G23.…”
supporting
confidence: 76%
“…These low mass hosts are weaker in their radio emission as well compared to those identified by other methods. A crossmatch with the low mass AGN hosts in GAMA G23 compiled by Salehirad et al (2022) also confirms that the SED-based low mass AGN hosts are unique to PROSPECT. Narrow-line diagnostics appear to struggle in identifying AGN in low mass galaxies.…”
Section: Discussionsupporting
confidence: 55%